Data on diet and growth by giant panda in zoo Negara, Malaysia - Ten, Dennis Choon Yung; Rohana, Jani; Ridza, Azizi; Mat Naim, Ramli; Yang, Haidi; Ahmad Nizam, Zainudin; Akmal Hadi, Samsuddin; Noor Hashida, Hashim; Mohd Noore, Afiq Ramle; Muhamad Aidil, Zahidin; Mohd Akmal, Mohd Raffi; Muhamad Safiih, Lola; et al. (Elsevier Inc, 2020)
In this data article we present the determinations of the diet preference and growth of a pair of the giant panda, Ailuropoda melanoleuca (David, 1869) from Zoo Negara Malaysia. Once considered as endangered, the captive giant pandas were given with nine species of local bamboo in separate indoor enclosures. We recorded data between May 25, 2014 and December 31, 2016 and analysed it based on food preference, the pattern toward food consumption and body weights using SPSS v25.0 (IBM, USA). Data on the bamboo preference, daily average bamboo provided and consumed, and factors predicting of body weight per individual are reported in this article. The data highlight correlation between panda growth (kg) to the part of bamboo consumed (kg) and exhibit the pattern of preferred part of food (i.e.: either the leaf, culm or shoots of bamboo variety) for panda consumptions. The food consumption toward the body weight was modelled using logistic regression analysis to help determine the pattern of food consumption and body weight of giant panda in the future and based on regression model 1, only consumed variable is significance to the model.